Legal Review Concerning Uncertified Land Rights in Bandung District - Agus Mulyono (IHSA Institute, 2022)
The legal process carried out by the community in case of a dispute by using mediation to resolve the problem in order to reach an agreement that is beneficial for both parties through negotiation. In the development of dispute resolution, the term Alternative Dispute Resolution (ADR) or Alternative Dispute Resolution Mechanism (MAPS) was used in Law Number 30 of 1999 concerning procedures for resolving disputes through ADR, namely as an institution for resolving disputes or differences of opinion through procedures agreed upon by the parties. with out-of-court settlements, one of which is through mediation, especially disputes over uncertified land rights. The objectives of the study are as follows: To find out the legal protection for uncertified land owners in Purwakarta Regency related to Government Regulation Number 24 of 1997 concerning Land Registration. To find out the settlement of disputes regarding ownership of land that has not been certified according to Government Regulation Number 24 of 1997 concerning Land Registration. The approach method is normative juridical, namely legal research conducted by reviewing and testing secondary data in the form of positive law. Specifications The research used is descriptive analytical, which systematically describes the facts and problems related to the legal aspects of land dispute resolution on uncertified land rights in Purwakarta Regency associated with PP. 24 of 1997 concerning Land Registration. The data obtained will then be analyzed in a qualitative normative manner. The legal protection of the parties for uncertified land rights in Purwakarta Regency is linked to PP No. 24 of 1997 concerning land registration is Article 32 paragraph (1) of Government Regulation Number 24 of 1997, that the certificate is a proof of rights that applies as a strong proof of physical data and juridical data contained therein, as long as the physical data and juridical data are in accordance with the data contained in the letter of measurement and the book of land rights in question. Settlement of land disputes over uncertified land rights in Purwakarta Regency is linked to PP No. 24 of 1997 concerning Land Registration. Land Dispute Settlement Solutions can be reached through the National Land Agency and solutions through the Judicial Body. Completion of the provisions of laws and regulations in the field of land, is not solely based on its juridical suitability but is also equipped with sociological, economic and political considerations.